The Effect Hydroquinone Extracted from Sonneratia caseolaris Fruit to Control Vibrio harveyi Artificial Infection on Tiger Shrimp, Penaeus monodon Fab. - . Arifuddin; . Sukenda; D. Dana (Jurnal Akuakultur Indonesia)
The role of hydroquinone extracted from Soneratia caseolaris fruit to control Vibrio harveyi infection on tiger prawn was carried out. In vitro experiment was conducted using disc diffusion and MIC {minimum inhibitory concentration) methods to know the sensitivity of V. harveyi to hydroquinone. Two kinds of in vivo experiments were (1) hydroquinone was injected into shrimps muscle and a week later the shrimps were challenged with V. harveyi (2) the shrimps were challenged with V. harveyi and one day later hidroquinone was injected. Total count of live V. harveyi on the shrimps and survival rate were observed after challenge test. Hydroquinone showed antibacterial activity with MIC at 3000 ppm. Hydroquinone injected shrimp showed higher survival rate compared with control (100% vs 50%). Total count of V. harveyi from injected shrimp, either before or after challenged, decreased by 2,61xl04 cfu/g and l,61xl04 cfu/g, respectively. These findings indicated that crude hydroquinone have anti-bacterial effect to control V. harveyi infection.